Polyelectrolytes to promote adhesive bonds of laser-structured aluminium. (September 2015) - Frenzel, Ralf; Schiefer, Tom; Jansen, Irene; Simon, Frank; Calvimontes, Alfredo; Grundke, Karina; Häußler, Liane; Beyer, Eckhard
Abstract: Aluminium is one of the most popular construction materials in machine and equipment manufacture as well as vehicle and aircraft construction. Particularly, in automotive and aircraft industries, the adhesive bonding of aluminium requires the pre-treatment of the adhesive surfaces. In this study laser pre-treatments were used to laterally control the surface roughness and clean the substrate surfaces by forming fresh aluminium oxide layers. In order to keep the adhesive properties stable over time, the laser pre-treated aluminium surfaces were subsequently coated with weak polyelectrolytes. The applied polyelectrolytes lower the driving forces for the adsorption of unwanted surface contaminations and provide reactive amino groups for the subsequent coupling of reactive adhesives. The surface topographies of the laser-treated aluminium surfaces were investigated in relation to the applied laser parameters (such as pulse frequency, and laser power) by means of scanning electron microscopy (SEM) and light-microscopic techniques (confocal microscopy). The adsorption of the polyelectrolytes was studied by X-ray photoelectron spectroscopy (XPS). Inverse water contact angle measurements using captive air bubbles were carried out to study the wettability (hydrophilicity/hydrophobicity) of the modified aluminium surfaces. Single lap joint tests carried out on joined AlMg3 sheets showed that the shear strengths can be significantly increased by pre-treatment with laser and coating of the alloy surfaces with weak polyelectrolytes. Furthermore, the application of polyelectrolytes improved the stability against corrosion. The article shows the increase of tensile shear strengths at adhesively bonded single lap shear samples after laser pre-treatment and also an increase in long-term stability due to of the combination of laser pre-treatment and coating with polyelectrolytes. Adhesive bonds of laser treated samples with and without polyelectrolyte coating have a higher stability against corrosion compared to untreated samples.